2016
DOI: 10.1007/s12017-016-8385-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Binding of [123I]CLINDE, a High-Affinity Translocator Protein 18 kDa (TSPO) Selective Radioligand in a Rat Model of Traumatic Brain Injury

Abstract: 2After traumatic brain injury (TBI), secondary injuries develop, including neuro-inflammatory 3 processes that contribute to long-lasting impairments. These secondary injuries represent computed tomography to image the neuro-inflammatory response after stroke. In this study, 10we used the same tracer in a rat model of TBI to determine changes in TSPO expression. 11Adult Sprague-Dawley rats were subjected to moderate Controlled-Cortical-Impact injury at 12 the M1 motor cortex, and sacrificed at 6h, 24h, 72h, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Information on the elevation of TSPO would be useful in detecting tumorigenicity of the transplanted hiPSC‐NS/PCs by carefully selecting when to perform the PET scan. For example, there is a dramatic increase in inflammation and associated activation of TSPO‐expressing microglia after TBI or SCI . Moreover, it has been reported that the activated Iba1 + microglia, which present a major cellular source of TSPO, peaks 42 days post‐SCI while TSPO expression peaks within a week or 72 hours after infarction, especially in the cerebral infarction models and the brain injury models, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information on the elevation of TSPO would be useful in detecting tumorigenicity of the transplanted hiPSC‐NS/PCs by carefully selecting when to perform the PET scan. For example, there is a dramatic increase in inflammation and associated activation of TSPO‐expressing microglia after TBI or SCI . Moreover, it has been reported that the activated Iba1 + microglia, which present a major cellular source of TSPO, peaks 42 days post‐SCI while TSPO expression peaks within a week or 72 hours after infarction, especially in the cerebral infarction models and the brain injury models, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a dramatic increase in inflammation and associated activation of TSPO‐expressing microglia after TBI or SCI . Moreover, it has been reported that the activated Iba1 + microglia, which present a major cellular source of TSPO, peaks 42 days post‐SCI while TSPO expression peaks within a week or 72 hours after infarction, especially in the cerebral infarction models and the brain injury models, respectively . In order to elucidate time‐dependent changes of TSPO expression after SCI in rodent models, we analyzed the gene expression of TSPO in mice at the nine days marker and 42 days marker after SCI using microarray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research concerning TSPO ligand uptake in animal models of TBI overwhelmingly supports the findings of its role as a microglia/macrophage activator. Specifically, studies have revealed that the increases of BP using 11C-PK11195 can be associated with both the time and type of brain injury [174][175][176]. Investigations using second-generation ligands fully support the results of the increased uptake in different types of trauma but are in contrast with the findings of increases of TSPO expression early after traumatic events [50].…”
Section: Tspo and Traumatic Brain Injuries (Tbis)mentioning
confidence: 96%
“…While the primary injury is the initial biomechanical trauma [ 50 ], a process involving neuronal, axonal and vascular damage induced by the kinetic energy, this induces a cascade of secondary processes leading to excitotoxicity, necrosis, apoptosis, autophagy and free radical formation [ 51 ]. Hence, TBI is considered to be a chronic disease [ 52 ], implicating that the pathophysiological and inflammatory processes in the brain take place at different times after the injury, where some are beneficial to recovery and others are generated by the injury and exaggerate the primary damage [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%